MOTIVASI MAHASISWA MEMILIH PROGRAM STUDI PG PAUD: Studi Kasus Pada Mahasiswa PG PAUD UNISRI - Sidik Nuryanto; Yetty Isna Wahyu Septiana; Wini Agustina (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2020)
Solo as a big city has many public and private campuses. UNISRI as one of the private campuses in the city of Bengawan. PAUD PG PAUD is a study program that was opened in 2014 at FKIP. As a new study program the distribution of students does not only come from the Solo residency, but also from outside Java such as (Kalimantan, Sumatra, and Nusa Tenggara). On the other hand the phenomenon of selection of teacher training programs has recently declined, bearing in mind that there are still many graduates who have not absorbed work. The purpose of this study is to describe students' understanding of the study program, as well as their motivation to study at PG PAUD UNISRI. This research uses a qualitative approach with descriptive methods. Data mining techniques using interviews, observation and documentation. The results of the study are students understanding study programs such as vision, mission, goals, graduate profiles through the website or brochure when registering to become new students. Internal motivation (1) profiles of PAUD teacher graduates, PAUD managers, dancers and musicians, APE developers as well as motion and song. (2) Achievement motivation where lectures are not just looking for a diploma but self-actualization. External motivation (1) Campus conditions include transportation access, lecturer quality and adequate and adequate infrastructure. (2) encouragement of parents who want their children to become PAUD teachers. Abstrak Solo sebagai kota besar memiliki banyak kampus negeri dan swasta. UNISRI sebagai salah satu kampus swasta yang ada di kota bengawan ini. PG PAUD merupakan Program studi yang dibuka pada tahun 2014 di FKIP. Sebagai program studi baru persebaran mahasiswanya tidak hanya berasal dari karisidenan Solo saja, namun berasal dari luar pulau jawa seperti (Kalimantan, Sumatra, dan Nusa Tenggara). Di sisi lain fenomena pemilihan program studi keguruan belakangan ini menurun, mengingat masih banyak lulusannya belum terserap kerja. Tujuan dari penelitian ini adalah mendeskripsikan pemahaman mahasiswa tentang program studi, serta motivasi mereka untuk kuliah di PG PAUD UNISRI. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Penggalian data dengan teknik wawancara, observasi dan dokumentasi. Hasil penelitian adalah mahasiswa memahami program studi seperti visi, misi, tujuan, profil lulusan melalui website atau brosur pada saat akan mendaftar menjadi mahasiswa baru. Motivasi internal (1) profil lulusan guru PAUD, pengelola PAUD, penari dan pemusik, pengembang APE serta gerak dan lagu. (2) Motivasi berprestasi di mana kuliah bukan hanya cari ijasah tapi aktualisasi diri. Motivasi eksternal (1) Kondisi kampus meliputi akses transportasi, kualitas dosen dan sarana prasarana yang sudah layak dan memadai. (2) dorongan orang tua yang menghendaki anaknya menjadi guru PAUD. Kata Kunci: Motivasi Mahasiswa, Kuliah, Pendidikan Guru PAUD